Associação entre duração do sono e características sociodemográficas, de saúde e emocionais em pessoas idosas da comunidade - Alves, Élen dos Santos (2022)
Sleep has been widely discussed in studies with the older population. Scientific evidence indicates that disorders related to poor sleep, poor sleep quality and sleep duration lead to several negative outcomes for the health of older people. Considered as a normal and necessary physiological condition for maintaining life, studies indicate that variables such as anxiety, stress, depression and cognition may be associated with sleep disorders in aging. The general objective of this thesis is to verify association between sleep duration and sociodemographic, health and emotional characteristics in older people in the community. Three studies were developed that make up the thesis. The first consists of a systematic review with the objective of identifying in the literature the existence of primary studies that evaluated the relationship and/or association between sleep and emotional factors in the older population. Searches were carried out in Pubmed, VHL, PsycINFO and Scopus, from 2010 to 2020, in Portuguese, English and Spanish. From a total of 1,354 articles identified, 32 studies were included for analysis. The data showed the association of emotional factors with the sleep of older people. Depressive symptoms, stress and anxiety were the most prevalent emotional factors and were associated with poor sleep quality, longer sleep latency, lower efficiency and duration, causing damage and triggering sleep disorders. The second study, with a cross-sectional method, aimed tocheck for differencesin depressive symptoms and perceived stress in old women, grouped according to sleep duration (short sleep, normal sleep and long sleep). Data from a database (2018) of a cross-sectional study carried out with 116 elderly women living in areas covered by Family Health Units were analyzed, using the following instruments: sociodemographic characterization questionnaire; Pittsburgh Sleep Quality Index; Geriatric Depression Scale – 15 items and Perceived Stress Scale. Analyzes were performed using the Pearson, Kruskall-Wallis and Mann-Whitney Chi-Square Tests. Old women with long sleep had a higher score in the evaluation of depressive symptoms compared to old women with short sleep and normal sleep. Perceived stress was significantly higher in the short sleep and long sleep groups. The third study, with a cross-sectional methodology, investigated direct and indirect associations between sleep duration and sociodemographic factors (gender, age, education and income), health (performance in basic and instrumental activities of daily living, use of medication, coffee intake, cognitive performance) and emotional aspects (symptoms of depression and stress) in community-dwelling older people, through the analysis of structural equations of Path Analysis. The independent variables male gender (-0.196); lower coffee consumption (-0.193) and worse cognitive performance (-0.187) were directly associated with longer sleep duration. Emotional aspects were mediated by functionality and cognition. It is concluded that several variables can directly or indirectly influence sleep duration. Indirect paths should be considered to enhance interventions in different areas of care for the older people. This thesis presents significantly relevant results. It adds that conditions often reported with aging may be related to causing negative outcomes for the health of the older people. The findings can contribute to fostering care strategies in the context of aging.